The European illustrated press and the emergence of a transnational visual culture of the news, 1842-1870 - Smits, Thomas (Routledge, Taylor & Francis Group, 2020)
"This book looks at the roots of a global visual news culture: the trade in illustrations of the news between European illustrated newspapers in the mid-nineteenth century. In the age of nationalism, we might suspect these publications to be filled with nationally produced content, supporting a national imagined community. However, the large-scale transnational trade in illustrations, which this books uncovers, points out that nineteenth century news consumers already looked at the same world. By exchanging images, European illustrated newspapers provided them with a shared, transnational, experience"--
Description based on online resource; title from digital title page (viewed on May 13, 2020)
Keywords: Weltausstellung -- 1867 -- Paris; Cassell's magazine -- London; Illustrirte Zeitung -- Leipzig; L' Illustration -- Zeitung; Geschichte 1842-1870; Journalism, Pictorial / Europe / History / 19th century; Illustrated periodicals / Europe / History / 19th century; European newspapers / Illustrations / History / 19th century; Art and society / Europe / History / 19th century; Berichterstattung; Illustration; Zeitschrift; Europa; Hochschulschrift